Analisis perkembangan kemampuan keuangan daerah pada Pemerintah Provinsi Sulawesi Utara tahun anggaran 2014-2018 - Keren Kezia Rejoice Adlin Mamangkey; Hendrik Manossoh; Heince Rudy Nicky Wokas (Indonesia Accounting Journal, 2020)
This study aims to determine how the development of regional financial capability in the North Sulawesi provincial government from its level of independence, level of dependency, decentralization ratio, and financial growth. The main characteristic of the region's ability to organize its government is the ability in its finances to finance the administration of the regional government. This type of research is qualitative research. Descriptive method is an analytical method used in this thesis research, that is every data - data obtained, analyzed based on theories relevant to the problem to be discussed to obtain the results of the analysis which is then concluded and provides advice. The results of descriptive analysis of the North Cellebes Province LRA APBD data show that from 2014 to 2018, the Regional Original Revenue development is still lacking, has not experienced a significant increase because Transfer Funds still dominate the Regional Revenue of North Cellebes Province. The conclusion is that there has been an improvement even though it is lacking, but based on the calculation of the financial ratios the Financial Ability is still in the near-able valuation.